Impact of COVID‐19 Infection on Patients with Cancer: Experience in a Latin American Country: The ACHOCC‐19 Study. (1st July 2021) - Ospina, Aylen Vanessa; Bruges, Ricardo; Mantilla, William; Triana, Iván; Ramos, Pedro; Aruachan, Sandra; Quiroga, Alicia; Munevar, Isabel; Ortiz, Juan; Llinás, Néstor; Pinilla, Paola; Vargas, Henry; et al.
Abstract: Introduction: The ACHOCC‐19 study was performed to characterize COVID‐19 infection in a Colombian oncological population. Methodology: Analytical cohort study of patients with cancer and COVID‐19 infection in Colombia. From April 1 to October 31, 2020. Demographic and clinical variables related to cancer and COVID‐19 infection were collected. The primary outcome was 30‐day mortality from all causes. The association between the outcome and the prognostic variables was analyzed using logistic regression models and survival analysis with Cox regression. Results: The study included 742 patients; 72% were >51 years. The most prevalent neoplasms were breast (132, 17.77%), colorectal (92, 12.34%), and prostate (81, 10.9%). Two hundred twenty (29.6%) patients were asymptomatic and 96 (26.3%) died. In the bivariate descriptive analysis, higher mortality occurred in patients who were >70 years, patients with lung cancer, ≥2 comorbidities, former smokers, receiving antibiotics, corticosteroids, and anticoagulants, residents of rural areas, low socioeconomic status, and increased acute‐phase reactants. In the logistic regression analysis, higher mortality was associated with Eastern Cooperative Oncology Group performance status (ECOG PS) 3 (odds ratio [OR] 28.67; 95% confidence interval [CI], 8.2–99.6); ECOG PS 4 (OR 20.89; 95% CI, 3.36–129.7); two complications from COVID‐19 (OR 5.3; 95% CI, 1.50–18.1); and cancer in progression (OR 2.08; 95% CI, 1.01–4.27). In the Cox regression analysis, the statistically significant hazard ratios (HR) were metastatic disease (HR 1.58; 95% CI, 1.16–2.16), cancer in progression (HR 1.08; 95% CI, 1.24–2.61) cancer in partial response (HR 0.31; 95% CI, 0.11–0.88), use of steroids (HR 1.44; 95% CI, 1.01–2.06), and use of antibiotics (HR 2.11; 95% CI, 1.47–2.95). Conclusion: In our study, patients with cancer have higher mortality due to COVID‐19 infection if they have active cancer, metastatic or progressive cancer, ECOG PS >2, and low socioeconomic status. Implications for Practice: This study's findings raise the need to carefully evaluate patients with metastatic cancer, in progression, and with impaired Eastern Cooperative Oncology Group status to define the relevance of cancer treatment during the pandemic, consider the risk/benefit of the interventions, and establish clear and complete communication with the patients and their families about the risk of complications. There is also the importance of offering additional support to patients with low income and residence in rural areas so that they can have more support during cancer treatment. Abstract : Considering the absence of data on the impact of COVID‐19 infection in cancer patients, the ACHOCC‐19 study was started in Colombia. Results are reported here.